Diversity of the endophytic fungi associated with the ancient and narrowly endemic neotropical plant Vellozia gigantea from the endangered Brazilian rupestrian grasslands. (April 2017) - Ferreira, Mariana C.; Cantrell, Charles L.; Wedge, David E.; Gonçalves, Vívian N.; Jacob, Melissa R.; Khan, Shabana; Rosa, Carlos A.; Rosa, Luiz H.
Abstract: This study focused on the taxonomy and diversity of the endophytic fungi associated with Vellozia gigantea, an endemic, ancient, and endangered plant species that occurs only in the rupestrian grasslands of Brazil. A total of 285 fungal isolates were recovered from leaves and roots of the V. gigantea, which were identified in 27 genera and 87 different taxa using molecular taxonomy methods. Xylaria berteri, Diaporthe sp. 1, Nigrospora oryzae, Muscodor sp. 1, Colletotrichum aeschynomene, and Trichoderma viride occurred in the highest frequency in both the leaf and root. Diaporthe was the most abundant genus, with 70 endophytic isolates recovered from the leaves and roots. Among all the taxa identified, 62 occurred as singlets, including those of the genera Clonostachys, Coccomyces, Crucellisporiopsis, Daldinia, Myxotrichum, Pallidocercospora, Pezicula, Peyronellaea, and Pseudocercospora . The diversity indices displayed high values, showing that V. gigantea shelters a diverse and rich mycobiota. Our results indicate that V. gigantea shelters in its tissues a highly diverse and cryptic mycobiota, including several rare species previously unreported as endophytes, but that are reported to have different ecological functions, which might be an important biological component contributing to the fitness of the plants living in the rupestrian grassland. Highlights: We examine the endophytic fungi of the endemic neotropical plant Vellozia gigantea . The diversity indices displayed that V. gigantea shelters a diverse and rich endophytic mycobiota. Our results indicate that V. gigantea shelters in its tissues a highly diverse and cryptic mycobiota.